A nosocomial outbreak of KPC‐2‐producing Klebsiella pneumoniae in a Chinese hospital: dissemination of ST11 and emergence of ST37, ST392 and ST395. (10th July 2013) - Yang, J.; Ye, L.; Guo, L.; Zhao, Q.; Chen, R.; Luo, Y.; Chen, Y.; Tian, S.; Zhao, J.; Shen, D.; Han, L.; Cantón, R.
Abstract In China, Klebsiella pneumoniae carbapenemase (KPC) ‐producing K. pneumoniae isolates have been identified. However, little is known about the spread and outbreak of KPC‐producing enterobacterial pathogens. In this study, 48 non‐duplicated KPC‐producing isolates were analysed for genetic relatedness by pulsed‐field gel electrophoresis (PFGE), antimicrobial susceptibility by E‐test, and sequence type (ST) by multilocus sequence typing. S1‐PFGE and Southern blot were used for plasmid profiling, and PCR and subsequent sequencing were performed to determine the effects of genetic background on the blaKPC gene. From December 2011 to June 2012, an outbreak of the KPC‐2‐producing K. pneumoniae was observed. The 48 isolates of K. pneumoniae are categorized into eight PFGE types (A1, A2, A3, A4, B, C, D and E). The predominant pathogens of the outbreak were strains with PFGE types A1, A2 and A3, which all belong to ST11. Furthermore, ST37, ST392 and ST395 KPC‐2‐producing K. pneumoniae isolates have also been sporadically identified. The blaKPC‐2‐carrying plasmids vary in size from 30 to 220 kb. The genetic environments of the blaKPC‐2 gene for most strains were consistent with the genetic structure of blaKPC‐2 on the plasmid pKP048. In conclusion, the dissemination and outbreak of KPC‐2‐producing K. pneumoniae isolates in this study appeared to be clonal, and ST11 K. pneumoniae was the predominant clone attributed to the outbreak. This is the first study to report the emergence and spread of KPC‐producing K. pneumoniae ST392 and ST395 worldwide. Our findings suggest that horizontal transfer of Tn3‐based transposons might mediate the spread of blaKPC‐2 gene between different K. pneumoniae clones in China.